An Encryption Approach Based on Formal Method for Securing Distributed Big Data Storage in Cloud Environment - Hassan, Anah Bijik; Boukari, Souley; Yau Gital, Abdulsalam; Abdulhamid, Mohammed (The Indonesian Journal of Computer Science, 2023)
Cloud computing is the technology used to store massive amounts of data (Big data) on Servers which locations are unknown to the user of the service. One of the major source of concern in security and privacy is the fact that cloud operators have chances to reach the sensitive data. This makes Cloud computing adoption by organizations with users’ sensitive details including the banking sector and government agencies marred by resentment. Therefore, a cryptography approach is proposed, named Secured Efficient Distributed Storage SecDcloud) model that is designed to obtain an efficient mass distributed service, and is supported by the Modified Alternative Data Distribution (MAD2) Algorithm Modified Secured Data distribution (MSED2) Algorithm as well as Improved Data Conflation (IDCon) Algorithm based on formal method. Our proposed mechanism aims to split, encrypt sensitive data and store the data to the different cloud servers without causing big overheads using formal method which prevents cloud service providers from directly accessing the user’s data. Our experiments, evaluated on security and efficiency of our technique, and is compared with state of the art Advanced Encryption Standard(AES) Algorithm and the results show that it is capable of effectively defending against the most common cloud-based threats while still maintaining a reasonable amount of processing time.